The feline humerus - Langley-Hobbs, S. J.; Straw, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The humeri of eleven feline cadavers were dissected and safe anatomical areas for placing external skeletal fixator pins were determined. Relevant measurements taken of the humeral condyle enabled a determination of a safe pin diameter range of 1.5 to 2.2 mm for transcondylar pins. Further anatomical measurements allowed recommendations to be made to angle pins in the distal humerus in a distolateral proximomedial direction so that the ESF pin penetrates the far cortex at least 20 mm proximal to the medial epicondyle in order to avoid pin penetration of the supracondylar foramen. Cross sections taken of the distal humerus revealed that passage of an IM pin into the medial aspect of the humeral condyle was possible in less than half the cases.
Keywords: Feline; humerus; external skeletal fixator; intramedullary pin